2022
DOI: 10.31018/jans.v14i3.3627
|View full text |Cite
|
Sign up to set email alerts
|

Edible cutlery: An eco-friendly replacement for plastic cutlery

Abstract: Plastic has become a significant threat to the entire ecological system, the daily utilization of plastic products has several beyond-description losses like air pollution caused by incinerating plastic, pollution of the marine environment and microplastics damaging internal organs of animals and indirectly harming humans by consuming the sea-food, meat and other products which rife with micro-plastic. This review aimed to assess the replacement of plastic usage with a better alternative, including studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…In addition to the several products mentioned before, edible cutlery is also one of the available alternatives for plastic cutlery. By meaning, edible cutlery is "a plant-based product in which meals can be served or taken as a meal itself" and is made of a mixture of flours (Roy and Morya, 2022). It is suggested that edible products are consumed right after being used to eat or drink.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the several products mentioned before, edible cutlery is also one of the available alternatives for plastic cutlery. By meaning, edible cutlery is "a plant-based product in which meals can be served or taken as a meal itself" and is made of a mixture of flours (Roy and Morya, 2022). It is suggested that edible products are consumed right after being used to eat or drink.…”
Section: A Introductionmentioning
confidence: 99%
“…Edible cutlery is a plant-based product made of various ingredients (usually some specific flours are used to get the desired attributes for the ultimate product) generally recognized as EBO (eco-friendly, biodegradable and organic) in which meals can be served or be taken as a meal itself (Roy and Morya, 2022). The product's attributes heavily influence customer's purchasing intentions towards certain products after several evaluations regarding the characteristics in terms of their values, beliefs, and past experiences (Peter & Olson, 2010).…”
Section: A Introductionmentioning
confidence: 99%
“…Since it doesn't truly require any more preparation, this edible cutlery is regarded as ready to eat. In contrast, they can decay in any kind of environment if they are not consumed because they don't require any particular circumstances to do so [4]. Ragi, also referred to as finger millet, is a commonly consumed millet in numerous regions of India and Africa [5].…”
Section: Introductionmentioning
confidence: 99%